2021
DOI: 10.3389/fcvm.2021.704208
|View full text |Cite
|
Sign up to set email alerts
|

Yes-Associated Protein in Atherosclerosis and Related Complications: A Potential Therapeutic Target That Requires Further Exploration

Abstract: Atherosclerosis and its complications diseases remain leading causes of cardiovascular morbidity and mortality, bringing a massive burden on public health worldwide. Atherosclerosis is recognized as chronic inflammation, and involves several highly correlated processes, including lipid metabolism dysfunction, endothelial cell dysfunction, inflammation, oxidative stress, vascular smooth muscle cell activation, platelet activation, thrombosis, altered matrix metabolism, and vascular remodeling. Within the past f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…While it remains elusive how arterial stiffening and the changes in ECM associated with stiffening cause VSMC activation, there is evidence that mechanical cues (as conveyed by changes in ECM stiffness) can impact gene expression and cellular function through intracellular mechanoresponsive proteins, such as transcriptional coactivator YAP (yes-associated protein). [8][9][10][11][12][13][14] ECM stiffening promotes the activation of YAP, which not only function as inducer of VSMC behavioral changes but also drives VSMC-dependent collagen deposition and further stiffening of the ECM, thus forming a positive-feedback loop to exacerbate the pathological outcome. 15,16 Indeed, the roles of YAP as mechanotransducer in mediating cell-ECM homeostasis in vasculature have been subjected to intensive investigation and study in recent years.…”
Section: Original Researchmentioning
confidence: 99%
“…While it remains elusive how arterial stiffening and the changes in ECM associated with stiffening cause VSMC activation, there is evidence that mechanical cues (as conveyed by changes in ECM stiffness) can impact gene expression and cellular function through intracellular mechanoresponsive proteins, such as transcriptional coactivator YAP (yes-associated protein). [8][9][10][11][12][13][14] ECM stiffening promotes the activation of YAP, which not only function as inducer of VSMC behavioral changes but also drives VSMC-dependent collagen deposition and further stiffening of the ECM, thus forming a positive-feedback loop to exacerbate the pathological outcome. 15,16 Indeed, the roles of YAP as mechanotransducer in mediating cell-ECM homeostasis in vasculature have been subjected to intensive investigation and study in recent years.…”
Section: Original Researchmentioning
confidence: 99%
“…EC activation is widely accepted as an important event in monocyte recruitment and the initiation of atherosclerosis [ 25 , 26 ]. To assess endothelial activation, sections of aortic sinus from 15 week old mice were immunostained with antibodies against p -selectin, E-selectin, VCAM-1 and ICAM-1.…”
Section: Resultsmentioning
confidence: 99%
“…Once activated, NF-κB induces the expression of a large number of inflammatory factors, such as IL-6 and tumor necrosis factor-α (TNF-α), and promotes the expression of various genes involved in plaque instability, such as adhesion molecules, endothelial nitric oxide synthase (eNOS), monocyte chemotactic protein-1 (MCP-1), and plasminogen activator inhibitor-1 (PAI-1) [37][38][39] . VSMC apoptosis is one of the key mechanisms of atherosclerotic plaque instability or even rupture, which also accelerates thrombosis [40,41] . In vitro experiments showed that OA inhibits the proliferation of VSMCs induced by angiotensin II, palmitate or TNF-α, thereby inhibiting atherosclerotic plaque growth.…”
Section: Alleviating Insulin Resistance and Atherosclerosismentioning
confidence: 99%